Review 3rd Ea

Download as pptx, pdf, or txt
Download as pptx, pdf, or txt
You are on page 1of 43

REVIEW

LAWS OF EXPONENT

PRODUCT LAW
• If m and n are positive integers and x is a real number, then

Example 1: x2·x4 = x2 + 4 = x6
Example 2: 2m3n2 · 4mn3 = (2·4)(m3·m)(n2·n3)
= 8m3+1n2+5 = 8m4n5
QUOTIENT LAW
CASE 1: m > n CASE 2: m < n CASE 3: m = n
(NEGATIVE EXPONENT LAW) (ZERO EXPONENT LAW)

Example: Example:
Example:

When equal numbers are subtracted, it will


(If case 1 is followed, the resulting result to zero. Any number raised to zero
exponent will be negative. To make the is equal to 1.
exponent positive, get the reciprocal then
change the negative exponent to positive
exponent.)
POWER LAW
CASE 1: (xm)n = xmn CASE 2: (xy)m = xmym CASE 3: (x/y)m = xm
Example:
Example: Example:

(x4)3 = x4·3 = x12 (xy)5 = x5y5


MULTIPLICATION OF
MONOMIALS
1. 5a3b2c · -4ab2c = (5·-4) (a3·a) (b2·b2) (c · c) = -20a4b4c2
2. -7xy · 6x3y5 = (-7·6) (x · x3) (y·y5) = -42x4y5
3. 3m5·8mn = 24 m6n
4. -3p5·-9p6 = 27p11
5. 12s8t4 · 5st = 60 s9t5
6. (5xy)2 = 25x2y2
7. (-3a2b3)3= -27a6b9
8. 4s(2s2t)3 = 4s(8s6t3) = 32s7t3
9. 3xy(2x2y)0 = 3xy(1) = 3xy
10. -9w5x ·4w2x = -36w5x + 2x = -36w7x
DIVISION OF MONOMIALS

1.

2.
3.
PRODUCT OF A MONOMIAL BY A
POLYNOMIAL

1. 2x (4x2 + 3) = 2x (4x2) + 2x (3)


= 8x3 + 6x
2. -3a2b (5a2b – 2ab + 6) = (-3a2b) (5a2b) + (-3a2b) (– 2ab) + (-3a2b) (6)
= -15a4b2 + 6 a3b2 – 18 a2b
3. 7uv3 (5u3v2 – 4u2v – 9uv) = 7uv3 (5u3v2) + 7uv3(– 4u2v) + 7uv3 (– 9uv)
= 35u4v5 – 28u3v4 – 63u2v4
PRODUCT OF TWO BINOMIALS
• In multiplying two binomials we shall employ the F.O.I.L. Method:
• (a + b) (c + d) = ac + ad + bc + bd

First Terms - ac
Outer Terms - ad
Inner Terms - bc
Last Terms – bd
PRODUCT OF SQUARE OF A BINOMIAL
Square of the sum of two terms:
(a + b) (a + b) = (a + b)2 = a(a) + a(b) + b(a) + b(b)
= a2 + ab + ab + b2 → combine like terms

Thus, (a + b)2 = a2 + 2ab + b2 (all three terms are positive)

Square of the difference of two terms:


(a – b) (a – b) = (a – b)2 = a(a) + a (– b) + (–b) (a) + (–b)(–b)
= a2 + (– ab) + (– ab) + b2 → combine like terms
Thus, (a – b)2 = a2 – 2ab + b2 (only the middle term is negative)
EXAMPLES:
1. (a + 3)2 = a2 + 2 (a)(3) + 32
= a + 6a + 9
2

2. (a – 3)2 = a2 + 2 (a) (–3) +(–3)2


= a2 – 6a + 9
PRODUCT OF THE SUM AND DIFFERENCE OF
TWO BINOMIALS

(a + b) (a – b) = a(a) + a(-b) + (b)(a) + (b)(-b)


= a2 + ab – ab – b2 → combine like terms
= a2 + 0 – b2 → opposite terms when added is
zero
= a2 – b2
Thus, (a + b) (a – b) = a2 – b2
Examples:
1.(2a + 3) (2a – 3) = (2a)2 – (32)
= 4a2 – 9
2. (x – 2y) (x + 2y) = x – (2y)
2 2

= x2 – 4y2
3. (5b2 + 6c) (5b2 – 6c) = (5b2 )2 – (6c)2
= 25b4 – 36c2
SPECIAL PRODUCTS

CUBE OF A BINOMIAL
(x + y)3 = x3 + 3x2y + 3xy2 + y3
Examples:
1. (2x + y)3 = 8x3 + 12x2y + 6xy2 + y3

2. (a + 5)3 = a3 + 15a2 + 75a + 125


FACTORING POLYNOMIALS WITH COMMON
MONOMIAL FACTORS

To factor a polynomial with a common monomial factor, express the given


polynomial as a product of the common monomial factor and the quotient
obtained when the given polynomial is divided by the common monomial
factor. In checking the result, the Distributive Property of Multiplication will
be applied.
Examples:
1. 15 +
2. – 16 – 2 + 12 = 𝟐(8𝑝− 1+ 6 )
FACTORING THE DIFFERENCE
OF TWO SQUARES
The binomial is called a difference of two squares, because a2 is the square
of a and b2 is the square of b. If we reverse this rule, we obtain a method
for factoring a difference of two squares. The factors of the difference of
two squares are the sum of the square roots of the first and second terms,
times the difference of their square roots.
Thus, the factors of 𝑎𝑟𝑒 (a + 𝑏 ) (𝑎 −𝑏 ).

(Note: To factor difference of two squares, it is helpful to know the perfect


square numbers. The number 100, for example is a perfect square,
because 100 = .)
Examples:

1. 16 – 81 = (4x + 9) (4x – 9)
2. – 9 = (+ 3) ( – 3)
3. 4 – 49 = (2x + 7) (2x – 7)
4. 64 – 121
FACTORING PERFECT SQUARE
TRINOMIALS (PST)
The square of a binomial is a Perfect Square Trinomial
(PST). Factoring the trinomial reverses the process.

STEPS:
1. Extract the square root of the first term.
2. Extract the square root of the last term.
3. Write these two terms as a binomial raised to the second
power, following the sign of the middle term of the PST.
Examples:
1. = or (x + 5) (x + 5)

2. 49
FACTORING THE SUM AND
DIFFERENCE OF TWO CUBES
The polynomial in the form is called the sum of two cubes because two
cubic terms are being added together and is called the difference of two
cubes because two cubic terms are being subtracted. Here are the
formulas that summarize how to factor the sum or difference of two cubes.
Study them carefully.
= (a + b)
= (a – b)
Note:
1. The binomial factor is the algebraic sum of the cube roots of the two
terms. 2. For the trinomial, the first and last terms are the squares of the
terms of the binomial factor. The middle term is the opposite of the product
of the terms of the binomial factor.
Examples:
1. = +
= (x + 3) [– (x)(3) + ]
= (x + 3) ( – 3x + 9)

2. 27 64 = -
= (3m - 4n) (3m)(4n) + ]
= (3m + 4n) (9m2 – 12mn + 16n2)
FACTORING QUADRATIC
TRINOMIALS OF THE FORM
, where a = 1
A quadratic trinomial is a trinomial in which the highest exponent of the
variable is 2. A quadratic trinomial is of the form where a, b, and c are
constants and a ≠ 0. The factors of a general quadratic trinomial are two
binomials.
In factoring Quadratic Trinomials , a = 1,
a. Factor the first term of the trinomial and write these factors as the first
terms of the factors;
b. List down all the factors of the last term and their sum;
c. Identify which factor pair sums up the middle term; then write each
factor in the pairs as the last term of the binomial factors.
Examples:
1. + 3x + 2 = (x + 1) (x + 2)
2. – 3x + 2 = (x – 1) (x – 2)
3. – 3x – 2 =(x + 1) (x – 2)
4. + 11x + 30 =(x + 5) (x + 6)
5. – 11x + 30 = (x – 5) (x – 6)
FACTORING QUADRATIC TRINOMIALS
OF THE FORM , WHERE A > 1
The value of a in a general quadratic trinomial can be greater than 1
(a > 1) and there are steps to be followed on how to get its factors.
STEPS:
a. Find the product of the leading term and the last term.
b. Find the factors of the product of the leading term and the last term
whose sum is equal to the middle term.
c. Rewrite the trinomial as a four-term expression by replacing the middle
term with the sum of the factors.
d. Group the terms with common factors.
e. Factor the groups using greatest common monomial factor.
f. Factor out the common binomial factor and write the remaining factor as a
sum or difference of the common monomial factors.
Examples:
1. Factor + 11x + 5
Solution:
a. Find the product of the leading term and the last term
+ 11x + 5
() (5) =
b. Find the factors of 10x2 whose sum is 11x.
(x) + (10x) = 11x
c. Rewrite the trinomial as a four-term expression by replacing the middle term with the sum of
the factors.
+ x + 10x + 5
d. Group the terms with common factors.
( + x) + (10x + 5)
e. Factor the groups using greatest common monomial factor.
x (2x + 1) + 5(2x + 1)
f. Factor out the common binomial factor and write the remaining factor as a sum or difference of
the common monomial factors.
(2x + 1) (x + 5)
2. – 5x – 2 3. – 12x + 5 4. – 17x + 6.
Solution: Solution: Solution:
a. – 5x – 2 a. – 12x + 5 a. – 17x + 6
() (–2) = () (5) = (5x2) (6) =
b. (–6x) + (x) = –5x b. (–2x) + (–10x) = – b. (–15x) + (–2x) = –
12x c. – 2x – 10x + 5 17x
c. – 6x + x – 2
d. ( – 2x) – (10x – 5) c. – 15x – 2x + 6
d. ( – 6x) + (x – 2)
e. 2x (2x – 1) – 5(2x – d. ( – 15x) – (2x – 6)
e. 3x (x – 2) + 1 (x – 1) e. 5x (x – 3) – 2(x – 3)
2)
f. (2x – 1) (2x – 5) f. (x – 3) (5x – 2)
f. (3x + 1) (x – 2)
Example 4. Factor 4x2 – 12x + 5. Solution: a. 4x2 – 12x + 5 (4x2) (5) =
20x2 b. (–2x) + (–10x) = –12x c. 4x2 – 2x – 10x + 5 d. (4x2 – 2x) – (10x – 5)
e. 2x (2x – 1) – 5(2x – 1) f. (2x – 1) (2x – 5) Thus, 3x2 – 5x – 2 = (3x + 1) (x
– 2).
APPLICATION
ONE SIDE OF A SQUARE MEASURES (4X2+7X−3)CM. WHAT IS THE
PERIMETER OF THE SAID SQUARE IN TERMS OF X?
THE LENGTH OF A
SIDE OF A SQUARE IS
GIVEN BY (5P+3) CM.
FIND THE
PERIMETER OF THE
SQUARE IN TERMS
OF P?
A RECTANGULAR POSTER
HAS DIMENSIONS (X + 7)
INCHES AND (2X - 3)
INCHES. WHAT IS THE
PERIMETER OF THE
POSTER IN INCHES?
A CLASS IS CREATING A
RECTANGULAR FRAME. THE
DIMENSIONS OF THE FRAME
MEASURES (3X - 5) CM AND
(X – 2) CM RESPECTIVELY,
WHAT IS THE PERIMETER OF
THE FRAME IN TERMS OF X?
A GROUP OF STUDENTS IS
WORKING ON A COLLABORATIVE
MATH PROJECT. THE LENGTH AND
WIDTH OF THE RECTANGULAR
BOARD WHICH WILL BE USED
MEASURES (6X + 2) CM AND (4X –
4) CM RESPECTIVELY. WHAT IS
THE AREA OF THE SAID
RECTANGLE IN TERMS OF X?
A RECTANGULAR DIGITAL
IMAGE HAS A WIDTH OF (X +
6) PIXELS AND A HEIGHT OF
(2X - 1) PIXELS. WHAT IS THE
TOTAL NUMBER OF PIXELS IN
THE IMAGE IN TERMS OF X?
A GROUP OF STUDENTS IS WORKING ON A
COLLABORATIVE SCIENCE PROJECT. THE TOTAL
AREA OF THEIR PRESENTATION BOARD IS
REPRESENTED BY THE POLYNOMIAL 4X² - 7X + 3
SQUARE FEET. DESPITE INITIAL SETBACKS AND
DISAGREEMENTS, THEIR SHARED LOVE FOR
SCIENCE AND THEIR RESILIENCE IN OVERCOMING
CHALLENGES LEAD THEM TO A SUCCESSFUL
PROJECT. IF ONE DIMENSION OF THE BOARD IS
(4X - 3) FEET, WHAT IS THE OTHER DIMENSION?
A RECTANGULAR SWIMMING POOL
HAS AN AREA GIVEN BY THE
POLYNOMIAL
12X² + 28X + 15 SQUARE FEET. IF
THE WIDTH OF THE POOL IS
(2X + 3) FEET, WHAT IS ITS LENGTH?

You might also like

pFad - Phonifier reborn

Pfad - The Proxy pFad of © 2024 Garber Painting. All rights reserved.

Note: This service is not intended for secure transactions such as banking, social media, email, or purchasing. Use at your own risk. We assume no liability whatsoever for broken pages.


Alternative Proxies:

Alternative Proxy

pFad Proxy

pFad v3 Proxy

pFad v4 Proxy